Flood-Irrigated Soybean Cost-Return Budget - O'Brien, Daniel M.; Dumler, Troy J.; Thompson, Curtis R.; Stockton, Roger (My University, 2001)
This publication projects a budget that reflects expected income and costs based on flood-irrigated soybean production.
MF577_2001_10
Keywords: MF577; Economics; Crops; MF